"The Book of Tribulations" : The Syrian Muslim Apocalyptic Tradition : An Annotated Translation by Nu'aym b. Hammad al-Marwazi /: The Syrian Muslim Apocalyptic Tradition : An Annotated Translation by Nu'aym b. Hammad al-Marwazi. (2017) - al-Marwazi, Nu'aym b. Hammad
No abstract available